Hemodynamic ,thyroid and immunomodulater effects of cannabinoid in rats. - Maulood, Ismail Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2016)
The aims of the present study are to investigate the cannabinoid effects on serum monocyte chemoattractant protein-1 (MCP-1), Troponin-1 ,liver and renal test parameters. The experimental rats were divided into three groups, the first group served as a control, and the animals were injected with normal saline. In the second group, animals were injected with cannabis (5 mg/kg, intraperitonial), while in the third group animals were injected with cannabis (10 mg/kg). After the course of the experiment, systolic blood pressure (SBP) tended to reduce significantly in the second dose of cannabis administered rats. Serum nitric oxide (NO) level slightly increased in dose dependent manner but it did not reach the level of significance. Serum level of malondialdehyde (MDA), troponin-T, MCP-1 and serum total bilirubin were significantly increased in the second dose of cannabis administration as compared to control rats. Neither triiodothyronin (T3) nor tetraiodothyronin (T4) hormones had statistically changed in cannabis group comparing with the control rats. Furthermore, serum uric acid reduced in cannabis group as compared with control. In conclusions, for the first time, our findings suggested that cannabis could affect immune system through MCP-1 elevation. As well as, cannabis may affect cardiac and liver functions via increasing troponin-T and bilirubin levels.
Keywords: Bloodpressure,Cannabinoid,Cannabis; Thyroid,MCP1